Atividade antifúngica de derivados hidrazino-tiazólicos contra Candida albicans - Lana Ivone Barreto Cruz (2019)
Candidiasis is an opportunistic fungal infection, being Candida albicans the most frequently isolated specie. Treatment of this infection is challenging because of the development of resistance during therapy and the limited number of antifungal compounds available. The aim of this study was to evaluate the antifungal activity of four thiazolylhydrazone-derived substances (1, 2, 3 and 4) by in vitro and in vivo tests and to study the possible effects of these on the virulence factors of C. albicans. Thiazolylhydrazone 1, 2, 3 and 4 showed antifungal activity, presenting MICs of 0.125 - 16.0 μg / mL against C. albicans. Toxicity of the substances was assessed using human erythrocytes and produced LC50> 64 μg / mL. When the ability to inhibit some virulence factors of C. albicans was evaluated, substance 1 was able to inhibit filamentation in a concentration equal to MIC; substances 1, 2 and 3 inhibited adhesion at a concentration related to MIC value and substances 1 and 2 disintegrated C. albicans biofilm. Substances were further evaluated using Galleria mellonella larva as an in vivo model. The survival of the larvae was increased when tested concentrations between 5 and 15 mg / kg, with as good as fluconazole performance. Substance 2 was evaluated in murine model of oral and systemic candidacy. In the oral model, substance 2 reduced the fungal load on rat tongue; and in the systemic model it reduced the fungal load found in the kidney when tested at 10 mg / kg. These results show that thiazolylhydrazones are an antifungal agent for C. albicans with in vivo efficacy.